2017
DOI: 10.1016/j.celrep.2017.07.053
|View full text |Cite
|
Sign up to set email alerts
|

NKX2-1 Is Required in the Embryonic Septum for Cholinergic System Development, Learning, and Memory

Abstract: SummaryThe transcription factor NKX2-1 is best known for its role in the specification of subsets of cortical, striatal, and pallidal neurons. We demonstrate through genetic fate mapping and intersectional focal septal deletion that NKX2-1 is selectively required in the embryonic septal neuroepithelium for the development of cholinergic septohippocampal projection neurons and large subsets of basal forebrain cholinergic neurons. In the absence of NKX2-1, these neurons fail to develop, causing alterations in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(111 citation statements)
references
References 52 publications
10
101
0
Order By: Relevance
“…The significant marker on chromosome 21 is adjacent to the genes PAX9 and NKX2-1 (Fig 7c). Previous works suggested that PAX9 is required for the chondrogenic differentiation of sclerotomal cells during embryogenesis [35, 36], and that NKX2 is required for the embryonic development of cholinergic septohippocampal projection neurons [37]. Moreover, according to PathCards, NKX2-1 is part of the embryo pre-implementation path [38].…”
Section: Discussionmentioning
confidence: 99%
“…The significant marker on chromosome 21 is adjacent to the genes PAX9 and NKX2-1 (Fig 7c). Previous works suggested that PAX9 is required for the chondrogenic differentiation of sclerotomal cells during embryogenesis [35, 36], and that NKX2 is required for the embryonic development of cholinergic septohippocampal projection neurons [37]. Moreover, according to PathCards, NKX2-1 is part of the embryo pre-implementation path [38].…”
Section: Discussionmentioning
confidence: 99%
“…The NKX2‐1 gene is expressed in the lung bud and thyroid primordium during embryogenesis and continues to be expressed in adult human lung and thyroid . In thyroid tissue, NKX2‐1 is instrumental in the formation of the thyroid bud and is important in the functional differentiation of the gland in late development and postnatally . In the lung, NKX2‐1 is a key regulator of pulmonary development and homeostasis, active in promotion of branching morphogenesis and epithelial lineage differentiation …”
Section: Discussionmentioning
confidence: 99%
“…17 In thyroid tissue, NKX2-1 is instrumental in the formation of the thyroid bud and is important in the functional differentiation of the gland in late development and postnatally. 27 In the lung, NKX2-1 is a key regulator of pulmonary development and homeostasis, active in promotion of branching morphogenesis and epithelial lineage differentiation. 28 A review of the genetics of NKX2-1 describes 77 known pathogenic variants.…”
Section: Discussionmentioning
confidence: 99%
“…The functional implications of molecular heterogeneity in striatal CINs are at present not well understood (Munoz-Manchado et al, 2018) (Lozovaya et al, 2018) (Magno et al, 2017). CINs originate from distinct areas of the subpallium which give rise to heterogeneous populations of cholinergic cells in the forebrain (Ahmed et al, 2019).…”
Section: Control Of the Cholinergic Cell Identitymentioning
confidence: 99%
“…Recent findings suggest that developmental differentiation factors induce some degree of functional diversity amongst CINs, thus enabling them to acquire unique properties (Magno et al, 2017) (Lozovaya et al, 2018) (Ahmed et al, 2019). However, the functional relevance of this heterogeneity remains unclear.…”
Section: Introductionmentioning
confidence: 99%